The Impact of Organizational Behavior on Firms’ Sustainable Performance: A Methodological Toolkit for Measurement - Mykhaylyova, Kateryna; Kichuk, Natalia; Prachov, Vitalii; Pugachov, Volodymyr (European Journal of Sustainable Development, 2025)
The performance of the organization in terms of enterprise management in the current conditions of globalization and transition on the digital is determined by organizational culture. This has an impact on employee productivity, the state of innovation, adaptability to change and resilience of the business in conditions of instability. The aim of the study is to examine technical approaches to evaluation of influence of the organization culture on efficiency of the enterprise under consideration based on the modern trends in the field of the information technology. The work is based on the methodological basis, i.e. the use of the qualitative analysis methods including the content analysis and the case studies. Specifically, existing methods for assessing organizational culture, especially qualitative methods in the field and staged quantitative methods in the laboratory, have limitations, largely related to subjectivity and insufficient adaptation of the latter’s quantitative techniques to the particularity of the corporations and industries examined. It is possible to use modern digital technologies for more objective assessment and at the price of significant staff and adaptation to the conditions of the enterprise. The work results can be used to create integrated methods of assessing the organizational culture forming, thus managing in question will become more efficient which enables enterprises to be more competitive. It has been demonstrated that a socially responsible company is a business structure that carefully adheres to the concept of sustainable development, stimulates innovation, and effectively manages available resources. It is necessary to conduct further research in the development of adaptive models for assessing the corporate culture in consideration of industry specifics, size of entities, and conditions of hybrid and remote work. Keywords: organizational culture, enterprise efficiency, corporate governance, assessment methods, digital technologies, Big Data, artificial intelligence, strategic management, sustainable development, corporate social responsibility.